SHORT NUTRITION STATUS (STUNTING) WITH DENTAL CARRIES IN PRESCHOOL CHILDREN IN SUKABUMI INDAH VILLAGE, BANDAR LAMPUNG CITY - Desi Andriyani; Arianto Arianto; Rudi Chandra (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: The problem of malnutrition in Indonesia is a health problem that has not been fully resolved by the government. Short nutritional status or stunting is a condition in which a person's height is less than normal based on age and gender. Height is one type of anthropometric examination and indicates poor nutritional status (malnutrition) in the long term/chronic. Stunting will have an impact on functional disorders such as cognitive abilities and poor academic achievement so that it can lead to a lack of income in the future, up to the loss of labor market productivity, which results in the loss of 11% of GDP (Gross Domestic Products) and reduces the income of adult workers by 20%. Objective: This study aims to determine the relationship between short nutritional status (stunting) and dental caries (dmft) in children preschool in Sukabumi Indah Village, Bandar Lampung City. Method: survey method with a cross-sectional approach, the sample of this study was children 3-5 years old in Sukabumi Indah Village, Bandar Lampung City totaling 150 children. The measuring instrument used was Microtoise staturemeter as well as dental examination status, data analysis Data analysis was carried out by calculating the Chi Square test. Result: Nutritional status with caries experience (dmft) had a significant relationship, where the mean dmfs in the stunted child group was 14.03 ± 6.16, while the mean dmfs in the normal child group was 7.47 ± 3.74 (p=0.0001). Conclusion: nutritional status affects the occurrence of caries.